Indonesian Learners’ L2 Reticence in English for Specific Purposes Classes and Its Influence on L2 Confidence - Dewi, Lusiana Puspita; Subekti, Adaninggar Septi (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
The present article reports on a research study on Indonesian English for Specific Purposes (ESP) learners' level of L2 reticence and its influence on L2 confidence. 213 ESP learners from different departments participated in this study. Data was collected through a survey. By means of descriptive statistics, it was found that learners generally reported a low-moderate level of L2 reticence. Most participants seemed unafraid of being the centre of attention or making mistakes in English class. Through bivariate linear regression, this study also found that L2 reticence significantly influenced L2 confidence. It accounted for 23.80% of the total variance in L2 confidence. Informed by these findings, pedagogical implications include incorporating class activities that allow more learner talk and the creation of a psychologically safe environment for learners to engage in risk-taking behaviours in L2 learning. Future studies might investigate the possible relationship between L2 reticence and other L2 learning aspects.